2009
DOI: 10.1128/jb.01829-08
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a Membrane-Bound Class III Adenylate Cyclase in Regulation of Anaerobic Respiration in Shewanella oneidensis MR-1

Abstract: Unlike other bacteria that use FNR to regulate anaerobic respiration, Shewanella oneidensis MR-1 uses the cyclic AMP receptor protein (CRP) for this purpose. Three putative genes, cyaA, cyaB, and cyaC, predicted to encode class I, class IV, and class III adenylate cyclases, respectively, have been identified in the genome sequence of this bacterium. Functional validation through complementation of an Escherichia coli cya mutant confirmed that these genes encode proteins with adenylate cyclase activities. Chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 40 publications
2
91
0
Order By: Relevance
“…Variations in expression were regarded as not significantly altered (NS) if the fold change was below 2 or the padj value was above 0.05. The expression data is compared with a study conducted by Charania et al (2009) The heme sites within the cytochrome pool are interconnected and therefore, addition of an electron acceptor to cells where electron storage sites are fully occupied leads to a complete reoxidation of the c-type cytochrome pool. Of note, a variety of different electron acceptors leads to a similar total reoxidation of the pool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variations in expression were regarded as not significantly altered (NS) if the fold change was below 2 or the padj value was above 0.05. The expression data is compared with a study conducted by Charania et al (2009) The heme sites within the cytochrome pool are interconnected and therefore, addition of an electron acceptor to cells where electron storage sites are fully occupied leads to a complete reoxidation of the c-type cytochrome pool. Of note, a variety of different electron acceptors leads to a similar total reoxidation of the pool.…”
Section: Discussionmentioning
confidence: 99%
“…CyaC is the major cyclic adenosine monophosphate adenylate cyclase and therefore involved in the synthesis of the effector molecule (Charania et al, 2009). Surprisingly, the cctA/fccA-deletion mutant was not affected in its transcription of essential c-type cytochromes such as mtrC, nrfA or cymA.…”
Section: The Respiratory Network In Shewanella Oneidensismentioning
confidence: 99%
“…BG167, a pilD mutant of S. oneidensis MR-1, was generated using the Mini-himar RB-1 transposon [27]. Chromosomal deletions of gspG, type IV pilus biogenesis, Msh pilus biogenesis, and flagellin genes were generated using the modified suicide plasmid pER2, a derivative of pDS3 [28] using described protocols [29]. DNA fragments for generation of deletions or complementation of mutants were amplified by PCR using Phusion polymerase (Clontech) and primers listed in Table 2.…”
Section: Mutagenesis Complementation and Protein Analysis Of S Oneimentioning
confidence: 99%
“…The class III adenylate cyclase was recently shown to regulate anaerobic respiration in S. oneidensis MR-1, and separate studies have shown that cyclic AMP (cAMP) levels were involved in the regulation of anaerobic respiration (8,44). Hence, SO3389 may be a sensor involved in the global regulation of different modulators for the up-and down-expression of genes related to shifts between aerobic and anoxic metabolism.…”
Section: Resultsmentioning
confidence: 99%